Characterization of defects generated by copper electrochemical plating process on silicon wafers / Yasmin Abdul Wahab - Abdul Wahab, Yasmin (2008)
With the rapid adoption of dual-damascene copper (CuDD) processing as semiconductor device features shrink into deep-submicron process, the copper electrochemical plating (ECP) is emerging as one choice for Cu metallization in multilevel interconnects. Copper processing has brought about an increased need to understand and predict desirable properties of the physical vapor deposition barrier and seed deposition, electroplating, chemical-mechanical polishing (CMP) as well as any thermal treatments that required stabilizing and annealing copper. Instead, defectivity is gaining momentum in Cu integration due to new Cu interconnects schemes and increasingly stringent process control requirements post some serious challenges in modem microelectronics devices. As a result, defectivity has driven a significant rise in process failure rates and has had a strong impact on the back-end-of- line (BEOL) processes. This project investigated the characterization of defects generated by copper electroplating process on He In-Situ and furnace annealed electro-plated copper films on p-type bare silicon wafers. A post ECP He In-Situ anneal processing was carried out over a 60°C to 180°C temperature range, with anneal duration times ranging from 6 seconds to 2 hours and the wafers began to be ramped at over 100°C with less than a minute soak time. For the furnace anneal, the wafers were loaded for almost an hour with less than 200 °C soak temperature. Specifically, impacts originated from the defects such as influences on yield lost are being investigated. This study improved a novel procedure of defect measurement, defect source analysis and static code analysis that was employed to identify the different types of defects generated progressively by post copper barrier seed, electrochemical plating, anneals and chemical mechanical planarization. To characterize the modes of action of defects in such processes, we employed constructive and analytical methods to analyze the interaction between defects from incoming and electroplating process and analyzing with scanning electron microscope (SEM) and covers process parameters perspective. Based on the design of experiments data, a new defect characterization scheme that takes defect generation mechanism and potential source into account has been proposed. The proposed scheme improves to differentiate between plating and CMP induced defects and flaws that were generally categorized as missing copper could have resulted from corrosion or scratches during polishing process from incomplete filling of fine features after plating. The study indicates the potential of right inspection and analysis approach of defects characterization can improve entire process modules and indirectly make CuDD technology production worthy.